2022
DOI: 10.3390/sym14051065
|View full text |Cite
|
Sign up to set email alerts
|

T-Stress Evaluation Based Cracking of Pipes Using an Extended Isogeometric Analysis (X-IGA)

Abstract: The aim of this study is to investigate the problem of pipe cracking based on T-stress analysis and the influence of other parameters, using a numerical computation performed by extended isogeometric analysis (X-IGA). This article examines the T-stress, which defines the second term of the Williams’ series expansion. T-stress provides effective elastic modeling at the crack tip. Using the extended iso-geometric analysis (X-IGA), we determined the distribution of T-stress at the crack tip in a pipe under intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…The statistics for this Special Issue related to published or rejected items were as follows [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]: 25 total submissions, 15 published papers (60%), and 10 rejected papers (40%). The geographical distribution of the authors of published papers is shown in Table 1, in which it can be seen that 50 authors are from seven different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…The statistics for this Special Issue related to published or rejected items were as follows [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]: 25 total submissions, 15 published papers (60%), and 10 rejected papers (40%). The geographical distribution of the authors of published papers is shown in Table 1, in which it can be seen that 50 authors are from seven different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%
“…A non-uniform rational B-splines (NURBS)-based isogeometric analysis (IGA) method [36] is implemented to satisfy the in-plane C 1 -continuity requirement of the SDF and further enhance the present method's applicability to complex plate geometries. In view of the remarkable precision and versatility, the SDF-based IGA method has significant potential in various applications, e.g., strain-based or stress-based reliability analysis, optimization design, fatigue analysis, and fracture analysis [37,38].…”
Section: Introductionmentioning
confidence: 99%